Photocatalytic Studies Of Bi2o3porous G-C3n4 Composite For Degradation Of Reactive Black 5 Under Uv-Vis Light Irradiation - Shafawi, Anis Natasha (2020)
Among all recent photocatalyst, g-C3N4 has received so much consideration in the degradation of organic pollutants. However, the use of bulk (pure) g-C3N4 faced the problems of high recombination of e-/h+ pairs and limited absorption of visible light due to its moderate band gap energy of about 2.7 eV. Pure g-C3N4 could be improved by structural modification and coupling with another semiconductor having moderate band gap energy such as Bi2O3 to develop new material for a better photocatalytic performance. For this purpose, Bi2O3/porous g-C3N4 composites with different loading of Bi2O3 (3-15 wt%) were successfully synthesized using thermal treatment and wet impregnation method. The specific objective of this study is to synthesize Bi2O3/porous g-C3N4 composite for the degradation of Reactive Black 5 (RB 5). Here, different process parameter studies were conducted and mechanism behind the degradation of RB 5 was studied. The successful synthesis of Bi2O3/porous g-C3N4 composites was proven using certain characterizations while optical properties were characterized using UV-Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS) and photoluminescence (PL). Moreover, further characterizations revealed that Bi2O3 particles were decorated on top of the porous g- C3N4 based on the Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) analysis, while High Resolution Transmission Electron Microscopy (HRTEM) analysis showed that intimate contact were formed between Bi2O3 and porous g-C3N4. In addition, the charge transfers indeed occurred as proven from XPS analysis. The photocatalytic activity of Bi2O3/porous g-C3N4 composites proved that 9wt% Bi2O3/porous g-C3N4 composite is the best photocatalyst with highest degradation percentage of RB 5 (84%) under 2 h of UV-visible light irradiation. Here, the most important criteria that contributed to dramatic improvement are due to the improved light absorption and separation of e-/h+ pairs, which were proven using UV-Vis DRS and PL analysis, respectively. Moreover, process parameter studies concluded that the highest degradation efficiency using 9wt% Bi2O3/porous g-C3N4 composite was achieved using 1 g/L of photocatalyst, 10 ppm of initial RB 5 aqueous solution and at pH 5.7. Besides that, radical scavenger test proved that the photo-generated charge carriers followed Z-scheme mechanism where superoxide radical (O2•-) was found as the most active species. And most importantly, the stability of 9wt% Bi2O3/porous g-C3N4 composite is preserved after being reused for multiple times (3 cycles) for the degradation of RB 5, in which 84%, 80% and 76% of RB 5 have been degraded at cycle 1, cycle 2 and cycle 3, respectively.